Perspectives of VA Primary Care Clinicians Toward Electronic Consultation-Related Workload Burden: A Qualitative Analysis - Lee, Marcie (JAMA Netw Open, 2020)
IMPORTANCE: Electronic consultation (e-consultation) is increasingly being adopted to expand access to specialty care and reduce health care costs. Little is known about clinicians’ perceptions of using e-consultations, which may be associated with program adoption. OBJECTIVE: To identify perceptions of primary care clinicians in the US Veterans Health Administration (VHA) system about e-consultation and workload. DESIGN, SETTING, AND PARTICIPANTS: A qualitative study using semistructured interviews was conducted from September 2017 through March 2018 in a national sample of VHA primary care clinics in the US. Participants were primary care clinicians who had at least 300 total patient encounters from July 2016 to June 2017, including at least 1 e-consultation request. A convenience sample of participants was recruited using email invitations. Deductive and inductive content analysis were used to identify themes. Data were analyzed from October 2017 to April 2018. EXPOSURES: Use of e-consultation. MAIN OUTCOMES AND MEASURES: Primary care clinician perspectives regarding e-consultation and their workload. RESULTS: A total of 34 primary care clinicians enrolled working across 27 VHA clinical sites were included; 9 (26%) were between ages 40-49 years; 23 (68%) were female. Three themes were identified. First, the process of entering, tracking, and following up on e-consultations added a time burden to primary care clinicians. Second, e-consultation was perceived to shift diagnostic and follow-up responsibilities from specialists to primary care clinicians. Third, e-consultations were thought to improve the timeliness and quality of care provided despite a perceived increase in workload. CONCLUSIONS AND RELEVANCE: In this study, participants perceived e-consultation as valuable for patient care but also as an increase in their workload. Further work is warranted to quantify the workload increase on clinician burnout, job satisfaction, and turnover.